Exploring Indonesian EFL teacher-student interactions in online learning - Siti Mafulah; Yazid Basthomi; Bambang Yudi Cahyono; Nunung Suryati (Studies in English Language and Education, 2023)
The use of online platforms has been shown to help students engage in learning writing. The student’s engagement in revising their writing draft can be seen from the interactions between the teacher and the students or among the students. This study aims to determine teacher-student interactions in a writing class conducted synchronously and asynchronously via Google Classroom, Google Meet, and WhatsApp. The data were derived from the teacher’s and students’ discussions posted in written and oral modes in the applications. A qualitative approach in designing and gathering the data was used in this study. The findings show that the interactions between the teacher and the students raised the students’ understanding of the teacher’s instruction so that the students were engaged in writing their drafts and revising them properly. The patterns of the teacher’s interactions can be categorised into giving feedback (39%) followed respectively by prescribing the editor role (17.7%), promoting individual contributions (13.3%), promoting joint construction of meaning and form (11%), thanking and praising (10%), guiding through the writing steps (5.7%) and stimulating students (3.3%). Students’ responses toward the teacher’s patterns of interaction depend on the teacher’s talk. There is no initiative from the students to start the discussion. The student’s background as freshmen can cause this; the first-year students may not be brave enough to start the discussion. This suggests that exploring the interactions between the teacher and students of different backgrounds is necessary.